Analiza ryzyka dokonywana na podstawie konwencji ramowej Rady Europy o sztucznej inteligencji na przykładzie zastosowań w sektorze prawnym - Więckowski, Zbigniew; Świerczyński, Marek (PRAWO i WIĘŹ, 2025)
The development of AI poses both opportunities and threats to human rights, democracy and the rule of law. In response to these challenges, the Council of Europe drafted the Framework Convention on Artificial Intelligence to establish a general legal framework for the use of AI. The Convention’s main principles include the requirement for risk assessment, the introduction of security measures, and liability for harm caused by AI. In the context of the legal sector, AI is being used, among other things, to analyze legal documents, automate routine tasks, predict the outcome of court cases, and create legal aid systems. However, the use of AI in the law raises challenges, such as the risk of bias, discrimination, invasion of privacy, and threats to the right to a fair trial. The AI Framework Convention emphasizes the need for compliance with human rights, as well as protection against the undesirable consequences of using AI in the administration of justice. HUDERIA (Human Rights, Democracy and Rule of Law Impact Assessment) is the Council of Europe’s proposed "tool" for assessing the impact of AI on human rights, democracy and the rule of law, which plays a key role in ensuring AI’s compliance with fundamental principles of justice.